The Effect of Home based Exercise on Treatment of Women with Poly Cystic Ovary Syndrome; a single-Blind Randomized Controlled Trial - Vasheghani-Farahani, Farzaneh; Khosravi, Shahrzad; Abedi Yekta, Amir Hossein; Rostami, Mohsen; Mansournia, Mohammad Ali (Novelty in Biomedicine, 2017)
Background: The most common reproductive endocrine disorder of reproductive age women is a Poly cystic ovary syndrome (PCOS) Metabolic syndrome has been more reported in patients with PCOS in comparison to general population. Few investigations have been performed to evaluate the independent effect of exercise on biochemical and clinical symptoms of patients with PCOS. The aim of the study was to find the effect of home base aerobic-strengthening exercises on anthropometric and hormonal variables of patients with PCOS. MaterialsandMethods:In this randomized controlled trial twenty women in the exercise group performed aerobic, strengthening exercises; the other 20 participants in the control group were advised to continue their previous physical activity pattern. Blood pressure, Waist to Hip ratio (WHR), BMI along with hormonal variables(including insulin related factors, sexual hormones and inflammatory factors) were assessed at baselineand after the 12 week intervention). Results:16patients in the exercise group and 14 patients in control group finished the study. TheWHR (p<0.001) along with the blood level of insulin (p=0.016), FBS (p=0.044), Prolactine (p=0.022) and hsCRP (p=0.035) and HOMA index (p=0.009) were decreased significantly in the exercise group compared with the control group. No significant differences were found in lipid profile and sexual hormones between groups at the end of the study. Conclusion:We can conclude that 12 weeks combined aerobic-strengthening exercise program in women with poly cystic ovary syndrome can lead to a reduction of waist to hip ratio (WHR) and some cardiovascular risk factors (including insulin, FBS, HOMA index and HsCRP) along with an increase of prolactine level in these patients.